Bibliometric overview of business & economics research - Merigó, José M.; Rocafort, Alba; Aznar-Alarcón, Juan Pedro (Journal of Business Economics and Management, 2016)
Bibliometrics is the quantitative study of bibliographic information. It classifies the information according to different criteria including authors, journals, institutions and countries. This paper presents a general bibliometric overview of the most influential research in business & economics according to the information found in the Web of Science. It includes research from different subcategories including business, business finance, economics and management. For doing so, four general lists are presented: the 50 most cited papers in business & economics of all time, the 40 most influential journals, the 40 most relevant institutions and the most influential countries. The results permit to obtain a general picture of the most significant research in business & economics. This information is very useful in order to identify the leading trends in this area.